Personal and occupational factors contributing to biomechanical risk of the distal upper limb among dairy workers in the Lombardy region of Italy. (February 2020) - Masci, F.; Rosecrance, J.; Mixco, A.; Cortinovis, I.; Calcante, A.; Mandic-Rajcevic, S.; Colosio, C.
Abstract: Biomechanical overload in the wrist flexor and extensor muscles, together with awkward hand positions during work activities, can result in occupational wrist and hand disorders. Dairy workers, specifically those that work in the milking parlor, are exposed to highly repetitive and forceful exertions of the upper limb throughout their work shift. There are very few studies that have investigated the determinants that contribute to the risk of distal upper limb musculoskeletal disorders among dairy workers. The purpose of the present study was to identify the variables affecting the biomechanical overload of the distal upper limb among milking parlor workers, define risk profiles, and propose possible interventions to reduce the high physical loads to the distal upper limb during milking activities. Forty male workers from the three most common milking parlor systems in Lombardy Italy were recruited to participate in this study. Multiple correspondence analysis of personal characteristics and occupational risk factors, followed by cluster analysis, led to the identification of three distinct groups of workers. Low, medium and high risk profiles were assigned to each group based on the risk assessments performed using the Strain Index and electromyography of the distal upper limb. The main risk determinants were workstation characteristics, work organization and milking routine. A well-organized milking routine, milking cluster weight below 2.4 kg or the use of supporting arms for the milking cluster may reduce the risk of biomechanical overload. Highlights: Dairy parlor workers may represent a population with high risk of musculoskeletal disorders. Risk determinants are workstation characteristics, work organization and milking routine. Three characteristic clusters of workers are identified based on risk determinants. Risk profiles for wrists' biomechanical overload in dairy workers are proposed.